ePortfolio practice for student well-being in higher education: A scoping review - McCarthy, Aslihan; Mitchell, Kate; McNally, Clare (Journal of University Teaching and Learning Practice, 2025)
The aim of the study was to map and assess published empirical studies on the contribution of ePortfolio practice to student wellbeing in higher education. Our leading research question was: What is known in the existing literature on the wellbeing outcomes of ePortfolio practice in higher education? A scoping review was conducted to identify affective outcomes of ePortfolio pedagogy. The review included 23 papers. Six thematic groupings around student well-being were identified among the included papers: ePortfolios for achieving human potential, ePortfolios leading to self-awareness, ePortfolios enhancing identity formation, ePortfolios supporting connectedness, ePortfolios fostering self-regulation, ePorfolios as stressors.